PENGARUH KEPRIBADIAN DAN PERBEDAAN GENDER TERHADAP PERENCANAAN KEUANGAN PRIBADI - Arifiyar Auzar A; Saiful Anwar; Tituk Diah Widajantie (Behavioral Accounting Journal, 2021)
This study wants to understand, test, and prove the impact of personality also gender differences on personal financial planning. This study implements the “quantitative approach”. The information’s collected in this study is using “primary data” that collected through questionnaire surveys directly. The sample in this research using “2016 UPN student Accounting department "Veteran" East Java”. Sample selection using the incidental sampling method. Data analysis uses “partial least square (PLS)” which uses “SmartPLS 3.2.9” for personality and gender hypothesis. The findings indicate that “personality variables” were having “significant effect” on “personal financial planning” while “gender variables” had “no significant effect” on “financial planning”.